Effects of Temperature and Concentration on the Determination of PET Viscosity - Silva,Felipe Z. da (2020)
This work describes the use of experiment planning to investigate the effects of the variables temperature and concentration of the polymer solution on the viscosity test of polyethylene terephthalate (PET). For this, the response surface methodology was based on a central composite rotatable design (CCRD) to optimize the combinations of the analytical conditions. With the analysis of the standard sample of PET with intrinsic viscosity of 0.630 ± 0.008 dL g-1 and 2-chlorophenol solvent, it was observed that the solution flow temperature and PET concentration caused significant effects on the results, while the storage temperature of the solvent was not statistically significant. With the results and the model developed, an industrial solid state polymerization process of PET was evaluated with simulations of the production of 30 tons of PET, demonstrating the importance of controlling the variables to guarantee the performance in quality control laboratories.